2017
DOI: 10.1127/anthranz/2017/0603
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in base of skull

Abstract: Sex determination is an important task in forensic medicine and physical anthropology. The aims of this study were to assess the presence of sexual dimorphism in the base of the skull and to compare the accuracy of sex estimation by this method with that achieved in other metric studies of this region. The sample comprised 109 individuals (53 males and 56 females) of known sex, age, and cause of death from San José cemetery in Granada (Spain). Six dimensions were analyzed and discriminant function analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Some of the studies conducted across the world show a sex prediction accuracy of 50.2%–90% (Table 7 ). 1 , 2 , 4 , 6 , 12 , 13 , 14 , 15 , 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies conducted across the world show a sex prediction accuracy of 50.2%–90% (Table 7 ). 1 , 2 , 4 , 6 , 12 , 13 , 14 , 15 , 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…The use of univariate and multivariate functions by anthropologists has suggested that the sexual identity from the cranial samples can be accurately established from 65% to 88%. 13 , 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Standard sex estimation in skeletal material is based on the analyses of the pelvis bones [ 12 ]. While additional features, such as skull shape, are also utilized additionally to standard sex determination methods, these features were found to be too indeterminate to be used on their own [ 13 ]. Molecular sexing using ancient DNA (aDNA) was applied for SM5.…”
Section: Methodsmentioning
confidence: 99%
“…e physical measurement method is to measure the physical object of the skull and establish a sex discriminant function. Some scholars have done a lot of research using this method and have achieved good results [10][11][12][13][14]. However, the biggest disadvantage of this method is that it may cause secondary damage to the skull during the measurement process, and the measurement results are not accurate enough due to human factors.…”
Section: Introductionmentioning
confidence: 99%